Translation of aspect in traditional and electronic dictionaries - Stanojević, Mateusz-Milan (2005)
In cognitive theory of translation, equivalence is defined as conceptualizing a scene using linguistic elements with the same degree of conventionality. Thus, equivalence is viewed as a process and not a product: there is no absolute one-to-one correspondence between a source and a target outside a particular context. Cognitive translation theory shares the non-algorithmic view of translation with the communicative model of translation. In this paper the cognitive claim that lexicon and grammar form a continuum of symbolic units of decreasing schematicity will serve as the basis of viewing the translation of grammar as the translation of culture. This will be taken as the basis of an attempt to build processuality into traditional and electronic dictionaries. Our claims will be exemplified on the example of translating grammatical aspect from Croatian to English.
Projekt MZOS
ENG